“Obrigado(a) por lembrar o meu nome”: uma cartilha de acolhimento de estudantes trans na escola - Macedo, Ingrid Pontes de (2024)
This dissertation narrates the experience of a teacher who, when trying to implement a pedagogical intervention against homophobia and transphobia in her school, find significant resistance from the school community. The detailed report explores the context, highlighting obstacles and social practices rooted in the school universe that made impossible the initially proposed activity. Resistance, permeated by prejudice, misinformation and fear, is the object of analysis here. In the face of obstacles, not only are the difficulties faced documented, but an innovative alternative is also proposed. A booklet, inspired by the experiences and a didactic sequence with the Gender and Diversity elective and other activities, will be outlined as a strategy to approach gender and sexuality in a broader and more inclusive way. This proposal aims to overcome the barriers identified in the initial experience, promoting a more effective educational approach with the aim of raising awareness among teachers. The inherent challenge of addressing gender and sexuality in education stands out, especially for humanities and sociology teachers. The researcher recognizes how this theme permeates not only professional practice, but also her own subjectivity. It is believed that the work can contribute not only to the understanding of school dynamics in the face of diversity issues, but also to reflection on the complexity inherent in teaching sensitive and challenging topics.